EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN OBAT PADA RUMAH SAKIT PANTI SECANTI GISTING - Lydia Sumiyati (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2011)
As a non-profit Panti Secanti Hospital Gisting face serious challenges in the midstof intense competition with other health institutions are growing rapidly and is oriented tothe achievement of profit. This study aimed to determine the implementation of internalcontrol system of drug supply at Panti Secanti Hospital Gisting. This is done as an effortto find solutions to the factors that can support the efficiency and effectivity of theHospital.The study reveals that internal control systems of medicines in the Nursing PantiSecanti Hospital Gisting was not in accordance with the princip les that apply generally.There are three things necessary to the attention of hospital management, theorganizational structure, narrative and segregation of duties procedures and systems.Third this has obvious need for achange and adjustment or repairas necessary. With themanagement changes are expected to provide positive impact and support the efficiencyand effectiveness of the Hospital.